A proximal radius of Barberapithecus huerzeleri from Castell de Barberà: Implications for locomotor diversity among pliopithecoids. Issue 157 (August 2021) - Arias-Martorell, Julia; Almécija, Sergio; Urciuoli, Alessandro; Nakatsukasa, Masato; Moyà-Solà, Salvador; Alba, David M.
Abstract: Pliopithecoids are a diverse group of Miocene catarrhine primates from Eurasia. Their positional behavior is still unknown, and many species are known exclusively from dentognathic remains. Here, we describe a proximal radius (IPS66267) from the late Miocene of Castell de Barberà (Vallès-Penedès Basin, NE Iberian Peninsula) that represents the first postcranial specimen of the pliopithecoid Barberapithecus huerzeleri . A body mass estimate based on the radius is compared with dental estimates, and its morphology is compared with that of extant and fossil anthropoids by qualitative means as well as by landmark-based three-dimensional geometric morphometrics. The estimated body mass of ∼5 kg for IPS66267 closely matches the dental estimates for the (female) holotype, thereby discounting an alternative attribution to the large-bodied hominoid recorded at Castell de Barberà. In multiple features (oval and moderately tilted head with a pronounced lateral lip and a restricted articular area for the capitulum; proximodistally expanded proximal radioulnar joint; and short, robust, and anteroposteriorly compressed neck), the specimen differs from hominoids and resembles instead extant nonateline monkeys and stem catarrhines. The results of the morphometric analysis further indicate that the Barberapithecus proximal radius shows closer similarities with nonsuspensory arboreal cercopithecoids and the dendropithecid Simiolus . From a locomotor viewpoint, the radius of Barberapithecus lacks most of the features functionally related to climbing and/or suspensory behaviors and displays instead a proximal radioulnar joint that would have been particularly stable under pronation. On the other hand, the Barberapithecus radius differs from other stem catarrhines in the less anteroposteriorly compressed and less tilted radial head with a deeper capitular fovea, suggesting a somewhat enhanced mobility at the elbow joint. We conclude that pronograde arboreal quadrupedalism was the main component of the locomotor repertoire of Barberapithecus but that, similar to other crouzeliids, it might have displayed better climbing abilities than pliopithecids.